PENGARUH PENGGUNAAN AIR BIASA, AIR KELAPA MUDA DAN AIR TEBU TERHADAP KUALITAS ROTI MANIS - Indriani, Ika; Syarif, Wirnelis; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This reserarch was based on use of different liquids, which is using mineral water, young coconut water and sugar cane water as ingredient of sweet bread. Kind of research is a pure experiment using a completely randomized design method with three repetitions. Used data are the primary data from 30 semi-trained panelist by submitting organoleptic test (a form) to see a quality of volume, shape color, aroma, texture and taste of sweet bread. We aralyzing data using ANAVA, if Fhitung > Ftabel, then proceed with duncan test. The result showed there was a significant influence on quality of the sweet bread, that is volume (doubled), shape(neat), shape(round symrtric), crust color (golden brown), crumbs color (creamy white), aroma (yeast), texture (soft), texturev(smooth), abd sweetness. The best percentage exists in the use of young coconut water on the production of sweet bread.Key word : Water, Coconut Water, Cane Water, Sweet Bread, Quality.